Measuring Religiosity of East Asians: Multiple Religious Belonging, Believing, and Practicing - Yang, Fenggang (Journal for the scientific study of religion, 2023)
Social surveys normally assume that respondents adhere to a single religious faith in belonging, believing, and practicing congruently. Some surveys even take religious identity as the singular measure of religiosity and examine its relationship with other variables. This practice, however, fails to capture nonexclusive and hybrid religiosity, which is arguably the traditional and normal pattern in East Asia while becoming increasingly common in the West. We have developed a new set of survey questions and conducted a survey among East Asian international students at an American university. The findings show that multiple religious belonging, believing, and practicing are quite common, the level of believing and participating in religions varies substantially, and no confession-based single measure of religious identity or practice is sufficient for measuring religiosity. We recommend this set of improved measures of religiosity be adopted in future surveys in East Asia and probably in the West as well.